(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to study the computerized accounting systems adopted globally, including the Enterprise Resource Planning (ERP) system, by employing them to control internal operations and tighten the financial and non-financial systems, and to demonstrate the impact of applying this system as one of the most important accounting information systems to achieve competitive precedence for the economic unit through its application in the Kufa Cement Factory. One of the factories of the Iraqi General Cement Company, and an explanation of its impact on administrative decisions that help reduce costs and work easily in addition to high flexibility and thus achieve competitive precedence in light of the rapid development in the contemporary business environment. To achieve this goal, when applying the enterprise resource planning system, the researcher relied on the data that the researcher obtained through field visits and reviewing the laboratory records for the year 2018, as well as conducting personal interviews with management and workers in the laboratory from all specialties, as the research adopted the applied method to test Research hypothesis and reach a set of conclusions, the most important of which are: • Implementing an enterprise resource planning system leads to identifying and measuring costs more fairly and achieves cost savings in addition to reducing time, speed of response, and flexibility in keeping pace with rapid changes. • Implementing an enterprise resource planning system provides useful information that helps workers calculate costs and distribute those costs more fairly, thus excluding costs that do not add value. The most important findings of the researcher can also be summarized in a set of recommendations, the most important of which is the need to pay attention to applying the enterprise resource planning system in the Iraqi industrial environment because it addresses the problems of archiving data and information necessary to manage costs and achieve competitive priorities